City transportation network vulnerability to disasters: the case of Hurricane Hermine in Florida. (27th May 2022) - Ghorbanzadeh, Mahyar; Koloushani, Mohammadreza; Ozguven, Eren Erman; Vanli, Arda; Arghandeh, Reza
ABSTRACT: Hurricanes affect millions of people in the U.S. every year and cause billion-dollar economic losses. Florida is one of the states in the U.S. which is vulnerable to hurricanes and major infrastructure damages were reported due to these extreme events such as Hurricane Hermine (2016). This study aims to assess the impacts of Hermine on the transportation network of Tallahassee, the capital of Florida, using a spatial-analytical approach and real-world hurricane data on roadway closures, power outages, power network configuration, and other storm-related variables. First, a geographic information systems (GIS)-based analysis was utilised to obtain the spatial patterns of hurricane-induced roadway closures along with power outages, power lines, downed trees, and the city's flood hazard zones. Second, a statistical model was developed to understand the association between the aforementioned variables and roadway closures. The spatial model results revealed that the roadway closures and power outages almost have the same patterns, and the city centre experienced more disruptions than other areas. The statistical model findings indicated that the power outages and power lines have strong relationships with roadway closures. The obtained knowledge of this study can provide valuable information for city officials to prepare better emergency policies for future potential hurricanes.